Prison state the challenge of mass incarceration - Useem, Bert (Cambridge studies in criminology, 2008)
During the past 25 years, the prison population in America shot upward to reach a staggering 1.53 million by 2005. This 2005 book takes a broad, critical look at incarceration, the huge social experiment of American society. The authors investigate the causes and consequences of the prison buildup, often challenging previously held notions from scholarly and public discourse. By examining such themes as social discontent, safety and security within prisons, and the impact on crime and on the labour market, Piehl and Useem use evidence to address the inevitable larger question, where should incarceration go next for American society, and where is it likely to go?